Bilobalide Exerts Anti-Inflammatory Effects on Chondrocytes Through the AMPK/SIRT1/mTOR Pathway to Attenuate ACLT-Induced Post-Traumatic Osteoarthritis in Rats - Ma, Tianwen; Lv, Liangyu; Yu, Yue; Jia, Lina; Song, Xiaopeng; Xu, XinYu; Li, Ting; Sheng, Xuanbo; Wang, Haoran; Zhang, Jiantao; Gao, Li (Frontiers in Pharmacology, 2022)
Although osteoarthritis (OA) significantly affects the quality of life of the elderly, there is still no effective treatment strategy. The standardized ginkgo biloba L. extract preparation has been shown to have a wide range of therapeutic effects. Bilobalide, a unique ingredient of ginkgo biloba, has anti-inflammatory and antioxidant pharmacological properties, but its mechanism of action on OA remains unknown. In this study, we investigated the effects of bilobalide on the development of OA through in vivo and in vitro experiments, as well as its potential anti-inflammatory mechanisms. The in vitro experiments demonstrated that bilobalide significantly inhibited the production of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), and matrix metalloproteinase 13 (MMP13) in ATDC5 chondrocytes induced by Interleukin-1β (IL-1β). At the molecular level, bilobalide induced chondrocyte autophagy by activating the AMPK/SIRT1/mTOR signaling pathway, which increased the expression of autophagy-related Atg genes, up-regulated the expression of LC3 protein, and reduced the expression of the p62 protein. In vivo, bilobalide exerted significant anti-inflammatory and anti-extracellular matrix (ECM) degradation effects in a rat model of post-traumatic OA (PTOA) induced by anterior cruciate ligament transection (ACLT). Bilobalide could relieve joint pain in PTOA rats, inhibit the expression of iNOS and COX-2 protein in cartilage via the AMPK/SIRT1/mTOR pathway, and reduce the level of ECM degradation biomarkers in serum. In conclusion, bilobalide exhibits vigorous anti-inflammatory activity, presenting it as an interesting potential therapeutic agent for OA.